Mind Your Grip: Even Usual Dexterous Manipulation Requires High Level Cognition - Guillery, Erwan; Mouraux, André; Thonnard, Jean-Louis; Legrain, Valéry (Frontiers in Behavioral Neuroscience, 2017)
Simultaneous execution of cognitive and sensorimotor tasks is critical in daily life. Here, we examined whether dexterous manipulation, a highly habitual and seemingly automatic behaviour, involves high order cognitive functions. Specifically, we explored the impact of reducing available cognitive resources on the performance of a precision grip-lift task in healthy participants of three age groups (18-30, 30-60 and 60-75 years). Participants performed a motor task in isolation (M), in combination with a low-load cognitive task (M+L), and in combination with a high-load cognitive task (M+H). The motor task consisted in grasping, lifting and holding an apparatus instrumented with force sensors to monitor motor task performance. In the cognitive task, a list of letters was shown briefly before the motor task. After completing the motor task, one letter of the list was shown, and participants reported the following letter of the list. In M+L, letters in the list followed the alphabetical order. In M+H, letters were presented in random order. Performing the high-load task thus required maintaining information in working memory. Temporal and dynamic parameters of grip and lift forces were compared across conditions. During the cognitive tasks, there was a significant alteration of movement initiation and a significant increase of grip force throughout the grip-lift task. There was no interaction with ‘age’. Our results demonstrate that planning and the on-line control of dexterous manipulation is not an automatic behavior and, instead, that it interacts with high-level cognitive processes such as those involved in working memory.